Behavior of biodegradable composites based on starch reinforced with modified cellulosic fibers. (15th May 2015) - Spiridon, Iuliana; Anghel, Narcis; Bele, Adrian
<x xml:space="preserve">Abstract</x> The aims of this study were to develop composite films based on potato starch and cellulose modified with toluenediisocyanate, to investigate their morphology and structure, and to evaluate their behavior to enzymatic hydrolysis and their potential use to manufacture of biodegradable seedling pots. The effects of modified cellulosic fibers upon mechanical properties and biodegradability of composite materials based on starch matrix were investigated by tensile strength tests, Fourier infrared spectroscopy, X‐ray diffraction, and dynamic vapor sorption. The behavior of the films to enzymatic hydrolysis with amylase and cellulase was studied; the kinetic of enzymatic hydrolysis and characterization of materials are reported. Chemical modification of cellulose improves tensile strength with about 47%, and decreases the biodegradability of composites making them more resistant to microbial attack, thus prolonging their shelf life. Copyright © 2015 John Wiley & Sons, Ltd.